Overcoming presynaptic effects of VAMP2 mutations with 4‐aminopyridine treatment. Issue 11 (1st October 2020) - Simmons, Roxanne L.; Li, Haiyan; Alten, Baris; Santos, Magda S.; Jiang, Ruiji; Paul, Brianna; Lalani, Sanam J.; Cortesi, Audrey; Parks, Kendall; Khandelwal, Nitin; Smith‐Packard, Bethany; Phoong, Malay A.; et al.
Abstract: Clinical and genetic features of five unrelated patients with de novo pathogenic variants in the synaptic vesicle‐associated membrane protein 2 (VAMP2) reveal common features of global developmental delay, autistic tendencies, behavioral disturbances, and a higher propensity to develop epilepsy. For one patient, a cognitively impaired adolescent with a de novo stop‐gain VAMP2 mutation, we tested a potential treatment strategy, enhancing neurotransmission by prolonging action potentials with the aminopyridine family of potassium channel blockers, 4‐aminopyridine and 3, 4‐diaminopyridine, in vitro and in vivo. Synaptic vesicle recycling and neurotransmission were assayed in neurons expressing three VAMP2 variants by live‐cell imaging and electrophysiology. In cellular models, two variants decrease both the rate of exocytosis and the number of synaptic vesicles released from the recycling pool, compared with wild‐type. Aminopyridine treatment increases the rate and extent of exocytosis and total synaptic charge transfer and desynchronizes GABA release. The clinical response of the patient to 2 years of off‐label aminopyridine treatment includes improved emotional and behavioral regulation by parental report, and objective improvement in standardized cognitive measures. Aminopyridine treatment may extend to patients with pathogenic variants in VAMP2 and other genes influencing presynaptic function or GABAergic tone, and tested in vitro before treatment. Abstract : A precision medicine approach to neurodevelopmental disorder in patients with mutations in the synaptic vesicle protein VAMP2 investigated variant effects on vesicle recycling and synaptic transmission in cellular models. A treatment strategy to enhance neurotransmission by increasing vesicle release was tested in vitro and in vivo.